ENT 300 The Donut Divas / Nunes Anak Stephen @ Jauk... [et.al] - Saji, Sharzalina; Abu Hajia, Sharmilla; Abdul Hamid @ Zaidi, nurul syahidah (2012)
There are criteria and condition that have to be fulfilled which require that involvement of effort and precision of producing our goods. Awareness of high quality foods is on the rise. Doughnut is the combination of nutritious ingredients because of the flavor, convenience, and luxury. Today’s consumer has less time to make a wholesome, handmade, but increasingly appreciates the nutritional benefits it provides. The Donut Divas will produce and sell high quality, handmade doughnut to the residents of Mukah area. The company will focus on fresh baked doughnut with high quality ingredients. The doughnut will be baked and sold at a storefront facility using a 4 deck, steam injected pastries oven and will be displayed in hygiene doughnut display cupboard. The Donut Divas main competition includes supermarket, health food store, and pastry shops around Mukah area. Its advantages lie in the high quality of our products due to specialization and artisan manufacturing. The main marketing focusing will be an eye catching sign and the scent of fresh doughnut. Moreover, doughnut or breads have many benefits compared to other carbohydrates- based foods. For instance, doughnut packaging is mobility and easy to serve. Without worrying about having a perfect cuts or shape, consumers can simply serve the doughnut and make another dish from the doughnut. The donut Divas is promising that our company will give consumer a big smile after walk out from our shop because we have given what they want and what they need plus the taste of our delicious special product.